Real-time tracking of delayed-onset cellular apoptosis induced by intracellular magnetic hyperthermia. (January 2016) - Blanco-Andujar, Cristina; Ortega, Daniel; Southern, Paul; Nesbitt, Stephen A; Thanh, Nguyễn Thị Kim; Pankhurst, Quentin A
Aim: To assess cell death pathways in response to magnetic hyperthermia.Materials & methods: Human melanoma cells were loaded with citric acid-coated iron-oxide nanoparticles, and subjected to a time-varying magnetic field. Pathways were monitored in vitro in suspensions and in situ in monolayers using fluorophores to report on early-stage apoptosis and late-stage apoptosis and/or necrosis.Results: Delayed-onset effects were observed, with a rate and extent proportional to the thermal-load-per-cell. At moderate loads, membranal internal-to-external lipid exchange preceded rupture and death by a few hours (the timeline varying cell-to-cell), without any measurable change in the local environment temperature.Conclusion: Our observations support the proposition that intracellular heating may be a viable, controllable and nonaggressive in vivo treatment for human pathological conditions.